A Multilevel Analysis of the Performance Implications of Excess Control in Business Groups - Yang, Kuo-Pin; Schwarz, Gavin M. (Organization Science, 2016)
A central premise of business groups is that controlling shareholders seize disproportionate control in excess of their ownership as a means of becoming and remaining competitive. We reexamine this axiom by exploring the relationship between excess control rights and performance outcomes in business groups. Using a sample of 106 Taiwanese business groups, we confirm that the effects of excess control in business groups are double edged, such that group-level excess control exhibits an inverted U-shaped relationship with group performance. At the same time, results show that when group-level excess control is high, there is a stronger negative relationship between firm-level excess control and firm performance. Moreover, the study indicates that the detrimental effect of excess control is less pronounced in business groups that are governed by family members or by professional managers. Findings offer a far deeper view than previously proposed on the excess control phenomenon in business groups, and the need to distinguish firm performance from group performance.